Xenotransplantation : science, ethics, and public policy (National Academy Press, 1996)
Xenotransplantation involves the transplantation of cells, tissues, and whole organs from one species to another. Interest in animal-to-human xenotransplants has been spurred by the continuing shortage of donated human organs and by advances in knowledge concerning the biology of organ and tissue rejection. The scientific advances and promise, however, raise complex questions that must be addressed. This book considers the scientific and medical feasibility of xenotransplantation and explores the ethical and public policy issues surrounding the possibility of renewed clinical trials. The volume focuses on the science base of xenotransplantation, public health risks of infectious disease transmission, and ethical and public policy issues, including the views of patients and their families.